Synthesis and Characterization of Cd(II) Complex of S4N3Cl - Singh Yadav, Surendra; Jadon, S.P.S. (Asian Journal of Chemistry, 2010)
Cadmium(II) complex of S4N3Cl was prepared by refluxing the mixture of S4N3Cl and cadmium acetate in DMF. The chemical data assigned the complex as S4N3Cl)2Cd(OOCCH3)2· The spectroscopic data infer that the complex is quadridentate coordinated complex having triclinic geometrical structure.